Hematopoietic stem cell transplantation in children with thalassemia: Brazilian Society of Bone Marrow Transplantation Consensus - Darrigo Junior, Luiz Guilherme; Vieira, Ana Karine; Kuwahara, Cilmara; Gouveia, Roseane Vasconcelos; Klinger, Paulo; Antunes, Alexandre de Albuquerque; Garcia , Julia Lopes (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Allogeneic hematopoietic cell transplantation (HCT) represents a critical therapeutic option for patients with transfusiondependent thalassemia (TDT), with thalassemia-free survival rates exceeding 90% in cases involving HLA-matched sibling donors. Due to the limited availability of matched donors, alternative sources such as HLA-matched unrelated donors, haploidentical donors, and umbilical cord blood have broadened HCT eligibility. Despite its potential for cure, HCT involves risks like graft-versus-host disease, graft rejection, and transplant-related mortality. Recent improvements in conditioning regimens have enhanced patient outcomes and quality of life. Factors affecting HCT success in TDT include recipient age, disease complications, effective chelation therapy, Pesaro score, and donor compatibility. This article aimed to update the Brazilian consensus established by the Brazilian Society of Cellular Therapy and Bone Marrow Transplantation in 2021, incorporating the latest advances in treating and managing TDT patients undergoing transplantation.